تحولات الروایة التاریخیة عند محمد فريد ابي حديد: The Historical Novel Changes According to Abu Hadid Muhammad Fareed - Nadia Bibi; Dr. Hafiz Haris Saleem (Al Manhal Research Journal, 2023)
The novel has a very great importance on the Arab and international levels. It is a modern literary art that came to our Arab world at the beginning of the nineteenth century from Europe. Our writers admired it and produced many novels that clearly expressed the Arab reality and also demonstrated the extent of Arab writers’ creativity in creating images. This study discussed the changes of the historical novel in Arabic literature, in form and content, according to Muhammad Farid Abu Hadid, who is considered one of the pioneers of writing historical novels in Egypt and the Arab world. Abu Hadid contributed significantly to the development of this novel art under his guidance and in particular, and these changings were represented in his good selection and use of topics. The novelist who revealed his strong feeling and high sense of belonging to his nation, he worked to revive Arab history and heritage and produced a group of historical novels, most of which revolve around ancient Arab life in the pre-Islamic era, and they are significant transformations in this early period, such as Abu Hadid, an example of the mediation between the historical novel. Traditionalism and the historical novel with a realistic orientation. Perhaps this was one of the biggest transformations that occurred in the historical novel in the period that followed Jeorgi Zydaan.This study reached a number of results, the most important of which is the statement of the connection between the development of the historical novel and the social, intellectual, and political conditions.